Desenvolvimento de Neomegalotomus parvus (Westwood, 1842) (Hemiptera: Alydidae) em planta alimentícia alternativa, Macroptilium atropurpureum Urb. (Leguminosae: Papilionoideae), em laboratório - Dantas Júnior, Ângelo Márcio Menezes (2009)
Neomegalotomus parvus (Westwood, 1842) (Hemiptera: Alydidae) is distributed in the neotropical region from Mexico to northern Argentina and Caribbean. In Brazil it has been reported in soybean and bean in the Cerrado biome. This species is known as " broad-headed bugs" because the nymphs mimic ants. the attack of this bug can transmit the fungus Nematospora coryles Peglion, which causes the "blight-yeast" disease which reduces the quality and crop yield. Macroptilium atropurpureum Urb (Leguminosae: Papilionoideae) is a leguminous plant, herbaceous and climbing, popularly known as siratro. Originally from Mexico, it was introduced in Brazil to be cultivated in association with grasses. However, due to the lack of control, it has become an invasive plant. In the field, the bugs were collected in M. atropurpureum in a vacant lot in the city of Maceió, Alagoas State (9°40'11.7"/S and 35°44'38.8"/W). We obtained 32 eggs and, after hatching, nimphs were isolated in containers made with 2 L PET bottles with 300mL final volume. And food (branches with green pods), wich was changed every three days. The N. parvus stadiums length in days, were [mean ± standard error, total amplitude (min-max), coefficient of variation (CV)]: embryonic period= 8.9 ± 0.2, 3(7-10) days, CV=11.4%; N1= 2.5 ± 0.1, 1(2-3) days, CV=20.4%; N2=5.2 ± 0.4, 8(4-12) days, CV= 35.0%; N3=3.9 ± 0.2, 3(3-6) days, CV=21.3%; N4= 4.6 ± 0.2, 3(4-7) days, CV= 19.4%; N5=9.7 ± 0.6, 9(5-14) days, CV=31.3%. The total development was 34.9 ± 0.8, 12 (28-40) days, CV=11.0%. The sex ratio was 0.5 indicating a balance between sexes. The viability of eggs was 100% and mortality during development was 31.2%. This performance with obtaining viable adults indicates that M. atropurpureum can be considered as an alternative plant-food.